Merkuri (Hg) di Permukaan Perairan Muara Sungai Banyuasin, Sumatera Selatan, Indonesia - Yulianto Suteja; Anna Ida Sunaryo Purwiyanto; Fitri Agustriani (Journal of Marine and Aquatic Sciences, 2019)
The purposes of this study were to determine the water quality, concentration and distribution of Hg in the surface water of Banyuasin river estuary. This research was conducted in June 2016 with 26 sampling stations. Measurement of in situ water quality was done using Conductivity Temperature Depth (CTD) multiparameter profiler while Hg metal was measured using Atomic Absorption Spectroscopy (AAS). The data obtained was interpolated by Inverse Distance Weighted (IDW) and then mapped spatially. The results showed that in general the water quality in Banyuasin river estuary still meets the seawater quality standards for marine biota based on KepMenLH no. 51 in 2004. The concentration of Hg in Banyuasin river estuary ranges from 0.001-0.032 mg/L with a distribution pattern that generally increases towards the ocean. The Hg concentration at the Banyuasin river estuary is on the maximum limit and exceeds the quality standard for marine biota.